PELAKSANAAN PERJANJIAN DANA PENSIUN LEMBAGA KEUANGAN BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 1992 TENTANG DANA PENSIUN - Ritanti Prasuseno (RECHTSTAAT, 2014)
ABSTRACTPT. Bank Negara Indonesia (Persero) Tbk. One is the founder and Pension Fund. The problems discussed in this research is how the implementation of the agreement, PT Pension Fund. Bank Negara Indonesia (Persero) in the main branches of Surakarta and legal consequences in case of breach of contract committed by one of the parties in the implementation of the agreement, PT Pension Fund. Bank Negara Indonesia (Persero) Tbk. The goal is to determine the implementation of the agreement, PT Pension Fund. Bank Negara Indonesia (Persero) Tbk in the main branches of Surakarta and legal consequences in case of breach of contract committed by one of the parties in the implementation of the agreement, PT Pension Fund. Bank Negara Indonesia (Persero).mplementation of the agreement, PT Pension Fund. Bank Negara Indonesia (Persero) started since reaching an agreement between the parties known of the existence of participant's signature on the membership application form and ending at the time of payment of pension benefits, either died or moved to another Pension Fund. In the event of default of the parties, the legal consequences for the Pension Fund is responsible for the harm done, whereas for participants who violate the agreement in the agreement then the agreement is declared null and void. In addition to the settlement of defaults can be settled amicably or through the Indonesian National Board of Arbitration (BANI).Key Word:Financial Institution Pension Fund